2021
DOI: 10.1001/jamanetworkopen.2021.21435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nonphysician Health Care Workers’ Burnout and Subsequent Changes in Work Effort

Abstract: IMPORTANCE Burnout is a pervasive, unrelenting problem among health care workers (HCWs), with detrimental impact to patients. Data on the impact of burnout on workforce staffing are limited and could help build a financial case for action to address system-level contributors to burnout. OBJECTIVE To explore the association of burnout and professional satisfaction with changes in work effort over 24 months in a large cohort of nonphysician HCWs. DESIGN, SETTING, AND PARTICIPANTS This longitudinal cohort study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…Within healthcare organizations, burnout has a direct impact on the ability to provide care. In a recent study of over 26,280 HCWs, researchers found that baseline burnout was associated with reduction in hours worked during the subsequent 24 months while satisfaction with the organization was associated with an increase likelihood of maintaining scheduled hours (Dyrbye et al, 2021 ). Nurse burnout has also been linked to nurse turnover.…”
Section: Significance Of the Problemmentioning
confidence: 99%
“…Within healthcare organizations, burnout has a direct impact on the ability to provide care. In a recent study of over 26,280 HCWs, researchers found that baseline burnout was associated with reduction in hours worked during the subsequent 24 months while satisfaction with the organization was associated with an increase likelihood of maintaining scheduled hours (Dyrbye et al, 2021 ). Nurse burnout has also been linked to nurse turnover.…”
Section: Significance Of the Problemmentioning
confidence: 99%
“…Healthcare workers stay in jobs and maintain work hours due to values alignment, perception of an equitable culture, job satisfaction, 2 and support for professional development. Leiter and Maslach found that retention relates to manageable workloads, work-life balance, feeling valued, work flexibility, salary, and benefits.…”
Section: Why Do People Stay In a Job?mentioning
confidence: 99%
“… 1 Indeed, all types of HCWs are departing their jobs, thus putting additional pressure on physicians and healthcare organizations. 2 Healthcare leaders, trying to reestablish viable frameworks for care after the pandemic, may be unaware of these changes. In this Viewpoint, we offer constructs to understand factors that lead physicians and other HCWs to resign, and provide suggestions as to how leaders can restore organizational loyalty and reduce turnover.…”
Section: Introductionmentioning
confidence: 99%
“…here has been a growing interest in burnout among health care providers and health professional students in the United States and across the world. [1][2][3][4][5][6][7][8][9][10][11] Burnout is associated with stress, inefficient work processes, and barriers to achieving meaning in one's work. [1][2][3][4]12 Concerns and studies related to health care worker burnout originated from the medical specialty.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Burnout is associated with stress, inefficient work processes, and barriers to achieving meaning in one's work. [1][2][3][4]12 Concerns and studies related to health care worker burnout originated from the medical specialty. Although physician burnout varies by specialty, the average rate of physician burnout is higher than the general population, with an increasing trend over time.…”
mentioning
confidence: 99%